2021
DOI: 10.5603/cj.a2019.0126
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high-density lipoprotein cholesterol on maximal lipid core burden indexing thin cap fibrous atheroma lesions as assessed by near infrared spectroscopy

Abstract: Background: Previous studies suggest that higher plasma concentrations of several lipid molecules are associated with higher lipid core burden index (LCBI) near infrared spectroscopy (NIRS) imaging. The aim of this study was to investigate whether an association between plasma lipids depends on plaque morphology (thin cap fibrous atheroma [TCFA] vs. non-TFCA) as measured by near-infrared spectroscopy-intravascular ultrasound (NIRS-IVUS). Methods: Sixty-four patients retrospectively enrolled were diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…One study demonstrated that the percent change in HDL-C was negatively associated with the percent change in maxLCBI 4mm after 13 months follow-up in patients with acute coronary syndrome or stable CAD [22] . Another study found a negative correlation between HDL-C and maxLCBI 4mm in patients with acute coronary syndrome or stable CAD with a maxLCBI 4mm ≥ 323, but not in patients with a maxLCBI 4mm < 323 [21] . In these two studies, 78 % and 85.7 % of the patients were on statin-therapy, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…One study demonstrated that the percent change in HDL-C was negatively associated with the percent change in maxLCBI 4mm after 13 months follow-up in patients with acute coronary syndrome or stable CAD [22] . Another study found a negative correlation between HDL-C and maxLCBI 4mm in patients with acute coronary syndrome or stable CAD with a maxLCBI 4mm ≥ 323, but not in patients with a maxLCBI 4mm < 323 [21] . In these two studies, 78 % and 85.7 % of the patients were on statin-therapy, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…To the best of our knowledge, this is the first study to investigate the association between a large number of lipoprotein subfractions and lipid content in coronary atheromatous plaques measured as maxLCBI 4mm by NIRS. Although hyperlipidemia, and particularly high levels of LDL-C, is considered a major risk factor for CVD, only a few studies have assessed the correlation or association between coronary lipid content measured as maxLCBI 4mm and traditional lipid measurements in patients with CVD [21] , [22] , [23] , [24] . One study demonstrated that the percent change in HDL-C was negatively associated with the percent change in maxLCBI 4mm after 13 months follow-up in patients with acute coronary syndrome or stable CAD [22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some findings from OCT studies show that TCFA is one of the characteristics of vulnerable plaques which are prone to rupture in coronary artery disease (31). Recently, TCFA was revealed to be associated with greater plaque burden and plaque volume (32). A study by Araki et al (33) also demonstrated that TCFA is a predictor of subsequent rapid plaque progression (OR=5.85; 95% CI, 2.01-17.03).…”
Section: Discussionmentioning
confidence: 99%